Preparation method of bismuth-based negative electrode material of sodium ion capacitor
By preparing the bismuth-based anode material of sodium ion capacitors, the coordination coupling between bismuth salt and dopamine hydrochloride and combined with the high-temperature carbonization process, the performance problems caused by the volume changes of the anode material in the sodium ion capacitor are solved, and the effects of high energy density and good cycle stability are achieved.
Patent Information
- Application Number
- CN202411885989.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
In sodium ion capacitors, the large ion radius of Na+ leads to slow electrochemical reaction kinetics and huge changes in the volume of the electrode material, resulting in no suitable negative electrode material that can accommodate high-speed repeated embedding and embedding of large-sized sodium ions, affecting long cycle performance and rate performance.
By dissolving the bismuth salt in a dilute aqueous nitric acid solution, adding dopamine hydrochloride to form a suspension, it is suction filtration, cleaning and vacuum drying, then heating under an inert atmosphere and maintaining constant temperature, and finally mixing with polyvinylpyrrolidone and carbonizing at high temperature, a bismuth-based negative electrode material of sodium ion capacitor is prepared.
The high energy density, good cycle stability and excellent rate performance of the bismuth-based anode material of sodium ion capacitor are achieved, with a capacity retention rate of nearly 100%, and an energy density of up to 140.1Wh kg-1.
Smart Images

Figure CN119724956A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material synthesis, and in particular relates to a method for preparing a bismuth-based negative electrode material for a sodium ion capacitor. Background Art
[0002] The world today is facing the dual challenges of the increasing depletion of traditional fossil energy and the worsening environmental problems. Therefore, it is urgent to develop new types of efficient and sustainable renewable energy. However, with the increasing market share of electric vehicles and energy storage systems, higher requirements are placed on the next generation of electrochemical energy storage devices: large capacity, fast charging, long life, good safety, and low cost. Sodium-ion capacitors are a new type of hybrid capacitor that has attracted much attention because of their high energy density of secondary batteries and the long cycle life and high power density of supercapacitors. However, Na + Large ionic radius This results in slow electrochemical reaction kinetics and huge changes in the volume of electrode materials, resulting in the lack of suitable negative electrode materials that can accommodate the high-rate repeated insertion and extraction of large-sized sodium ions. Therefore, the design and development of high-capacity and high-rate negative electrode materials is the key to the development of sodium ion capacitor energy storage devices.
[0003] Among the many negative electrode materials, alloy-based negative electrodes (Ge, Sb, Sn, etc.) have attracted widespread attention due to their advantages such as high theoretical capacity, suitable working potential and abundant resources. Among them, bismuth (Bi) has a very high theoretical capacity (386 mAhg -1 ) and volumetric capacity (3765mAh cm -3 ) and a suitable sodium alloy reaction potential at 0.5V, therefore, bismuth has been proven to be a very promising negative electrode material for SIC. However, during the sodium bismuthification process, due to volume expansion (≈244%), the bismuth negative electrode will inevitably be pulverized, causing the solid electrolyte interface (SEI) to be continuously destroyed and formed, resulting in continuous consumption of the electrolyte, thus affecting the long cycle performance and rate performance. Therefore, in order to achieve the unique physical and chemical properties of sodium ion capacitors, it is necessary to design the bismuth negative electrode with appropriate structure and function.
[0004] Generally, the composite of metallic bismuth and carbon-based materials is an effective strategy to improve the electrochemical performance of bismuth. Among them, carbon-based materials include carbon, carbon nanotubes and graphite. These composite materials can establish interconnected electron transfer pathways, thereby promoting charge transfer and ensuring fast kinetics. For example, Chen et al. (Adv. Energy Mater. 2024, 2400132.) innovatively encapsulated a flower-like micro-sized bismuth in an elastic nitrogen-doped carbon framework (FBi@NC). This design enables the FBi@NC negative electrode to reach 2.86 g cm -3High tap density and at 1mAcm -2 Provides 1100mAh cm -3 Li et al. (ACS Appl. Energy Mater. 2023, 6, 3071-3080.) prepared bismuth nanoparticles encapsulated in nitrogen-doped porous carbon frameworks (Bi@NPC) by chemical precipitation. -1 It can still deliver 243.9mAh g at 2000 cycles. -1 Xue et al. (Nano Lett. 2019, 19, 1998-2004.) fabricated Bi@NC composite materials and achieved a stable reversible capacity at a current density of 1A g -1 The specific capacity of the battery is 302 mAh g when the cycle exceeds 1000 times. -1 .
[0005] These studies have shown that designing bismuth nanostructures can alleviate the significant volume expansion that occurs during charge and discharge, maintain the continuity between bismuth particles during the reversible sodium / de-sodium process, and thus enhance the electron transport of bismuth-based anode materials. More importantly, the nanostructure reduces the internal stress of bismuth particles and shortens the diffusion / transmission distance of ions / electrons, thereby significantly enhancing the cycle stability of bismuth anodes. However, future research needs to further explore the storage mechanism of sodium ions and the relationship between the electrochemical properties of bismuth-based materials and the microstructure of carbon materials. In addition, the low yield, particle aggregation, increased production cost and complexity, and reduced Coulomb efficiency of the preparation process of bismuth-based anode materials seriously hinder their application. Therefore, establishing a strong interface connection between carbon-based materials and metallic bismuth through a simple synthetic route will be very promising to improve the electrochemical performance of bismuth-based anode materials and have certain practical application value. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a method for preparing a bismuth-based negative electrode material for a sodium ion capacitor with simple preparation, high cycle stability, high first coulombic efficiency and high capacitor energy density.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A method for preparing a bismuth-based negative electrode material for a sodium ion capacitor comprises the following steps:
[0009] Step (1), dissolving the bismuth salt in a 0.5M dilute nitric acid aqueous solution, stirring until completely dissolved, to obtain a solution A; in the solution A, the concentration of the bismuth salt is 0.005-0.03 g mL -1 ;
[0010] Step (2), adding dopamine hydrochloride to the solution A obtained in step (1), and stirring at 50-70° C. to form a light yellow suspension B;
[0011] Step (3), after filtering, washing and collecting the suspension B obtained in step (2), the obtained light yellow powder is placed in a vacuum dryer at 75-85° C. to obtain a dried sample C;
[0012] Step (4), the sample C obtained in step (3) is heated at 5-10°C min under an inert atmosphere. -1 The temperature is raised to 100-400°C at a constant rate and maintained at a constant temperature for 0.5-3h, then cooled to form a gray-black powder D;
[0013] Step (5), the black powder D obtained in step (4) is mixed with polyvinyl pyrrolidone and then ground. The obtained sample is incubated at 5-10°C min under an inert atmosphere. -1 The temperature is increased at a rate of 600-900° C. and maintained at a constant temperature for 0.5-3 h, and then cooled to obtain a bismuth-based negative electrode material for a sodium ion capacitor.
[0014] The bismuth salt described in step (1) is one or a mixture of two or more of bismuth nitrate, bismuth chloride, bismuth citrate, and bismuth acetate;
[0015] In step (2), the mass ratio of dopamine hydrochloride to bismuth salt is (0.5-3):1.
[0016] The inert atmosphere in steps (4) and (5) is one or a mixture of two or more of nitrogen, argon, and hydrogen-argon mixed gases;
[0017] In step (5), the mass ratio of black powder D to polyvinyl pyrrolidone is (1-5):1.
[0018] The sodium ion capacitor bismuth-based negative electrode material prepared by the above method was assembled into a sodium ion half-cell and then heated to 0.1A g -1 The current density can reach 350-390mAh g -1 High reversible capacity; at a current density of 1Ag -1 After 1000 cycles, the capacity remains at 347.6 mAhg -1 The capacity retention rate is close to 100%, and after being pre-sodiumized and assembled with activated carbon positive electrode into a sodium ion capacitor, the energy density of the sodium ion capacitor is as high as 140.1Whkg -1 .
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The negative electrode material prepared by this method has high energy density, good cycle stability and excellent rate performance.
[0021] 2) The present invention is prepared by simple chemical precipitation and high temperature carbonization process, the preparation process is simple and the raw material resources are abundant. 3+ The micron-sized Bi@NC negative electrode material is prepared by coordination coupling. The loose porous nitrogen-doped carbon structure provides sufficient buffer space for the volume change of nano-metal bismuth during the sodium ion insertion / extraction process, improving its cycle stability. In addition, the loose porous nitrogen-doped carbon structure has a larger specific surface area, providing a unique electron transmission pathway and sodium ion transmission channel, further improving the energy density, cycle stability and signal performance of sodium ion capacitors. The prepared bismuth-based negative electrode material has high specific capacity and high stable cycle performance (1Ag -1 After 1000 cycles, the capacity retention rate is 100%), high first coulombic efficiency (ICE: 78.54%) and high energy density, which are better than the sodium storage performance of Bi@C composite materials reported in recent years, and achieve efficient and stable sodium storage.
[0022] 3) The negative electrode material prepared by this method is used in sodium ion capacitors, which have high energy density, cycle stability and rate performance. The energy density of the Bi@NC electrode material after pre-sodiumization and assembly with activated carbon positive electrode into a sodium ion capacitor is as high as 140.1Wh kg -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention is a flow chart for preparing the bismuth-based negative electrode material for the sodium ion capacitor.
[0024] Figure 2 This is the XRD diagram of the bismuth-based negative electrode material of the sodium ion capacitor in Example 1.
[0025] Figure 3 This is a SEM image of the bismuth-based negative electrode material of the sodium ion capacitor in Example 1.
[0026] Figure 4 This is the TGA diagram of the bismuth-based negative electrode material of the sodium ion capacitor in Example 1.
[0027] Figure 5 This is the EIS graph of the bismuth-based negative electrode material of the sodium ion capacitor in Example 1.
[0028] Figure 6 This is a charge and discharge curve diagram of a sodium ion half-cell assembled from the bismuth-based negative electrode material of a sodium ion capacitor in Example 1.
[0029] Figure 7 This is a rate capability diagram of a sodium ion half-cell assembled from the bismuth-based negative electrode material of a sodium ion capacitor in Example 1 at different current densities.
[0030] Figure 8The bismuth-based negative electrode material of the sodium ion capacitor of Example 1 is 1Ag -1 Long cycle performance diagram at different current densities.
[0031] Fig. 9 This is a charge and discharge curve diagram of a sodium ion capacitor assembled from a bismuth-based negative electrode material and an activated carbon positive electrode in Example 1.
[0032] Fig.10 This is a charge and discharge curve diagram of a sodium ion half-cell assembled from the bismuth-based negative electrode material of a sodium ion capacitor in Example 2.
[0033] Fig.11 This is a charge and discharge curve diagram of a sodium ion capacitor assembled from a bismuth-based negative electrode material and an activated carbon positive electrode in Example 2.
[0034] Fig.12 This is a charge and discharge curve diagram of a sodium ion capacitor assembled with a bismuth-based negative electrode material and an activated carbon positive electrode in Example 3. DETAILED DESCRIPTION
[0035] The present invention will be described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0036] The basic process of the preparation method of a bismuth-based negative electrode material for a sodium ion capacitor of the present invention is as follows: Figure 1 shown.
[0037] Example 1
[0038] A method for preparing a bismuth-based negative electrode material for a sodium ion capacitor comprises the following steps:
[0039] First, prepare a bismuth salt with a concentration of 0.015 g mL -1 Dilute nitric acid aqueous solution, that is, add 0.45g of bismuth nitrate to 30mL of 0.5M dilute nitric acid aqueous solution, stir for a period of time to completely dissolve the solid matter; then add 0.585g of dopamine hydrochloride, stir at 60℃ for 6h to form a light yellow suspension; filter the suspension, wash and collect the obtained light yellow powder, dry it at 80℃ and simmer at 5℃min under an inert atmosphere. -1 The temperature was raised to 300 °C at a constant rate and maintained for 2 h before cooling; the black powder was then mixed and ground with polyvinyl pyrrolidone at a mass ratio of 3:1, and the obtained sample was heated at 5 °C min in an argon mixed atmosphere. -1 The temperature was raised to 800°C at a constant rate and maintained for 2 h before cooling;
[0040] Depend on Figure 2 It can be seen that the spectrum corresponds to the standard card ICDD No. 01-044-1246, indicating that the Bi@NC composite material was successfully prepared.
[0041] Figure 3 This is the SEM image of the sample prepared in Example 1. There are several unique structures in the Bi@NC material. One is the carbon-coated Bi spheres with nanometer diameters. The other is that these Bi spheres are wrapped by porous carbon. Since the carbon-coated bismuth material has very excellent electrical conductivity, it can provide a good electron transmission channel for the main material Bi. The presence of C can also improve the transmission of ions in the main material Bi, thereby enhancing the high-rate capability of Bi.
[0042] Depend on Figure 4 It can be seen that the bismuth content of the bismuth-based negative electrode material of the sodium ion capacitor is as high as 85%.
[0043] Depend on Figure 5 It can be seen that sodium ion capacitors have a smaller charge transfer impedance, which is conducive to electron transmission.
[0044] Depend on Figure 6 It can be seen that the bismuth-based negative electrode material of sodium ion capacitor is 0.05Ag -1 It has a high reversible capacity at a low current density and a first coulombic efficiency of up to 78.5%.
[0045] Depend on Figure 7 It can be seen that the bismuth-based negative electrode material of sodium ion capacitor is 10Ag -1 Before the current density reaches 10A, the capacity has almost no attenuation, indicating that the Bi@NC material has excellent structural stability. -1 And return to 0.1Ag -1 When the battery is discharged, the capacity is slightly higher than that when it is just discharged, which shows that the material has very excellent rate performance, which is due to its good conductive properties.
[0046] Depend on Figure 8 It can be seen that the bismuth-based negative electrode material of sodium ion capacitors has a current density of 1Ag. -1 After 1000 cycles, there is still 347.6 mAhg -1 reversible capacity.
[0047] The sodium ion capacitor prepared in this embodiment and the sodium ion capacitor assembled with the bismuth-based negative electrode material and activated carbon has a capacity of 140.1 Wh kg -1 The highest energy density, such as Fig. 9 shown.
[0048] This example successfully constructed a high-performance, low-cost, and long-cycle-life bismuth-based negative electrode material for sodium-ion capacitors. Thanks to the unique structure of the composite material, Bi@NC has a high -1After 1000 cycles at the current density, the capacity retention rate is close to 100%; in addition, the energy density of the sodium ion capacitor assembled with the bismuth-based negative electrode material and the activated carbon positive electrode is 140Wh kg -1 .
[0049] Example 2
[0050] First, prepare a bismuth salt with a concentration of 0.005 g mL -1 Dilute nitric acid aqueous solution, that is, add 0.15g of bismuth chloride to 30mL of 0.5M dilute nitric acid aqueous solution, stir for a period of time to completely dissolve the solid matter; then add 0.48g of dopamine hydrochloride, stir at 70℃ for 6h to form a light yellow suspension; filter the suspension, wash and collect the obtained light yellow powder, dry it at 80℃ and simmer at 10℃min under an inert atmosphere. -1 The temperature was raised to 200 °C at a constant rate and maintained for 2 h before cooling; the black powder was then mixed and ground with polyvinyl pyrrolidone at a mass ratio of 1:1, and the obtained sample was heated at 10 °C min in a nitrogen mixed atmosphere. -1 The temperature was raised to 900°C at a constant rate and maintained for 3 hours before cooling;
[0051] Fig.10 It can be seen that the bismuth-based negative electrode material of sodium ion capacitor is 0.1Ag -1 The current density is 391.2 mAh g -1 High reversible capacity and first coulombic efficiency of up to 70.6%. The sodium ion capacitor assembled with bismuth-based negative electrode material and activated carbon prepared in this embodiment has a capacity of 137.6Whkg -1 The highest energy density, such as Fig.11 shown.
[0052] Example 3
[0053] First, prepare a bismuth salt with a concentration of 0.03 g mL -1 Dilute nitric acid aqueous solution, that is, add 0.9g of bismuth citrate to 30mL of 0.5M dilute nitric acid aqueous solution, stir for a period of time to completely dissolve the solid matter; then add 2.7g of dopamine hydrochloride, stir at 50℃ for 6h to form a light yellow suspension; filter the suspension, wash and collect the obtained light yellow powder, dry it at 75℃ and simmer at 5℃min under an inert atmosphere. -1 The temperature was raised to 400 °C at a constant rate and maintained for 1 h before cooling; the black powder was then mixed and ground with polyvinyl pyrrolidone at a mass ratio of 1:5, and the obtained sample was heated at 5 °C min in an argon / hydrogen mixed atmosphere. -1 The temperature was raised to 600°C at a constant rate and maintained for 1 hour before cooling;
[0054] The sodium ion capacitor monomer assembled with the bismuth-based negative electrode material and activated carbon prepared in this embodiment has a capacity of 105.39 Whkg -1 The highest energy density, such as Fig.12 shown.
Claims
1. A method for preparing a bismuth-based negative electrode material for a sodium ion capacitor, characterized in that: The following steps are involved: Step (1), dissolving the bismuth salt in a 0.5M dilute nitric acid aqueous solution, stirring until completely dissolved, to obtain a solution A; in the solution A, the concentration of the bismuth salt is 0.005-0.03 g mL -1 ; Step (2), adding dopamine hydrochloride to the solution A obtained in step (1), and stirring at 50-70° C. to form a light yellow suspension B; Step (3), after filtering, washing and collecting the suspension B obtained in step (2), the obtained light yellow powder is placed in a vacuum dryer at 75-85° C. to obtain a dried sample C; Step (4), the sample C obtained in step (3) is heated at 5-10°C min under an inert atmosphere. -1 The temperature is raised to 100-400°C at a constant rate and maintained at a constant temperature for 0.5-3h, then cooled to form a gray-black powder D; Step (5), the black powder D obtained in step (4) is mixed with polyvinyl pyrrolidone and then ground. The obtained sample is incubated at 5-10°C min under an inert atmosphere. -1 The temperature is raised to 600-900° C. at a constant rate and maintained at a constant temperature for 0.5-3 hours, and then cooled to obtain a bismuth-based negative electrode material for a sodium ion capacitor; In step (2), the mass ratio of dopamine hydrochloride to bismuth salt is (0.5-3):1; In step (5), the mass ratio of black powder D to polyvinyl pyrrolidone is (1-5):
1.
2. The method for preparing a bismuth-based negative electrode material for a sodium ion capacitor according to claim 1, characterized in that: The bismuth salt described in step (1) is one or a mixture of two or more of bismuth nitrate pentahydrate, bismuth chloride, bismuth citrate and bismuth acetate.
3. According to the method for preparing a bismuth-based negative electrode material for a sodium ion capacitor according to claim 1 or 2, the inert atmosphere in steps (4) and (5) is one or a mixture of two or more of nitrogen, argon, and a hydrogen-argon mixed gas.